Colonial encounters in Southwest Canaan during the Late Bronze Age and the Early Iron Age - Ḳokh, ʿIdo (Culture and history of the ancient Near East, 2021)
Introduction -- Dawn -- The Egyptian network -- Goddess in translation: the Fosse Temple at Lachish -- Ambivalence -- Collapse -- Regeneration -- Reorientations -- In the eye of the beholder -- Summary.